INTEGRATED APPROACH TO THE MANAGEMENT OF PATIENTS WITH THE USE OF MIDWIFERY PESSARIES DOCTOR ARABINO WHEN ADMINISTERED PREGNANT WOMEN WITH HIGT RISK FOR PRETERM DELIVERY - Баринов, Сергей Владимирович; Шамина, Инна Васильевна; Ралко, Вячеслав Владимирович; Лазарева, Оксана Вячеславовна; Шкабарня, Людмила Леонидовна; Дудкова, Галина Владимировна; Клементьева, Людмила Леонидовна; Мельник, Ирина Владимировна; Владимирова, Ольга Вячеславовна (Mother and Baby in Kuzbass, 2017)
The purpose of research – to improve the results of pregnancy and birth outcomes in pregnant women at high risk of miscarriage by applying the obstetric pessary doctor Arabino.Subjects and methods. In order to assess the effectiveness of midwifery pessary doctor Arabino, we have analyzed the course of pregnancy and birth outcome (n = 82), in the group of women at high risk of miscarriage and premature birth, which was established this obstetric pessary up to 22 weeks.Results. Analysis of pregnancy and birth outcomes in a group of women at high risk of miscarriage, which was established this obstetric pessary showed that the leading place in the structure of extragenital occupied diseases of urinary system (25,6 %), cardiovascular system (17,1 %), in women with abnormally located placenta (35,4 %) in 62,1 % of cases marked by the migration of the placenta up to 26-27 weeks during treatment of obstetric pessary. In 86,7 % of cases pregnancy ended urgent delivery, preterm birth 24-35 weeks was 10,9 %. Complications such as bleeding during childbirth and the postpartum period, we did not observe.Conclusion. The use of obstetric pessary doctor Аrabino in combination with progesterone in the management of high-risk pregnant women prevents premature termination of pregnancy in women with cervical incompetence, uterine fibroids, multiple pregnancy, pregnancy after IVF. The percentage of fixed-term births in this group was 86,7 %. In the group of pregnant women with abnormally located placenta during treatment with obstetric pessary in 62,1 % of cases marked by the migration of the placenta up to 26-27 weeks of bleeding during childbirth and the postpartum period are not mentioned
Keywords: obstetric pessary; premature labor; cervical incompetence; abnormal location of the placenta